重症筋無力症 - 本村, 政勝 (神経治療学, 2016)
Myasthenia gravis (MG) is an autoimmune neurological disorder characterized by impaired neuromuscular transmission due to circulating pathogenic autoantibodies. MG patients produce pathogenic autoantibodies against the acetylcholine receptors (AChR), muscle–specific receptor tyrosine kinase (MuSK), and low–density lipoprotein receptor–related protein 4 (Lrp4) which are localized on the postsynaptic membrane of the neuromuscular junction. This lecture provides the overview of MG in Japan including classification, epidemiology, autoantibodies, clinical manifestation, diagnosis, treatment, and prognosis, especially focusing on the new standard treatment approach according to novel MG diagnostic criteria suggested by the MG clinical guidelines for 2014. Treatments for MG are based on immunotherapy by steroids and immunosuppressants. In Japan, treatments include cholinesterase inhibitors, thymectomy, steroids, immunosuppressants, plasma exchange, and intravenous immunoglobulin therapy. However, even when utilizing all of these treatments, the proportion of MG patients achieving complete stable remission is less than 10%. The new treatment approach suggests the combination therapy from early disease stage, to reduce the risk of crisis and disease progression. The current goal of MG treatment is firstly to treat MG patients to achieve pharmacological remission as rapidly as possible using the above therapies at onset. The therapeutic protocol according to onset age, disease type, and pathogenic autoantibodies conducted in Nagasaki University Hospital is also discussed.